ANALISIS FAKTOR PENENTU KEIKUTSERTAAN PETERNAK SAPI POTONG DALAM KELEMBAGAAN KELOMPOK TANI TERNAK - Agustina Abdullah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
This study aimed to analyze the factors affecting the participation of farmers in farmer group institution. Source of research data is primary data and secondary data. Sampling county, district, village or farmer groups done purposively. Selection of respondents cattle ranchers done by random of each farmer group. The research variables are the characteristics of farmers, farm characteristics, government policies, the environmental carrying capacity of the farm, as well as the membership status of farmers in farmer groups. Data were analyzed using factor analysis, principal component analysis (PCA), as well as path analysis (path analysis) and structural equation modeling (SEM). The results showed the most decisive factor participation of farmers to be active and participate in farmers groups strongly influenced variable access and the services provided by the extension agent, aged farmers, feeding system and the experience of raising, information about government programs and assistance provided, as well as the number of family and labor potential that exists in the family farmer.